Program Verification: Vision and Reality. - Vardi, Moshe Y. (Communications of the ACM, 2021)
The author discusses the concept of verification in computing and computer programs, particularly concerning the costs and benefits of autonomous systems paired with machine learning. He references the work of computer scientists Tony Hoare and Amir Pnueli.